Analysis of nail withdrawal strength in roof system - Mohd Afif, Abdullah (2012)
Current record show that failure due to wind storm in Malaysia has been increasing year by year. This natural disaster has a lot of negative impact especially to the public property. There are many factor to this failure occurs. From previous study, typical structure damage due to wind storm is roof and truss. Therefore, objective of this study is to determine the shear stress nail to the wood in roof connection system. There are three types of wood and two different size of nail will be tested. This study focus on examined the effect of types of wood and nail withdrawn force with specific depth. Result from this study determined that the higher the specific gravity of wood will increase the resistance shear force. The result also shown that increasing the depth of nail will increase the capacity force. It can be concluded that specific gravity and depth of nail is important to resist uplift force.